Bone Mesenchymal Stem Cell-Derived Extracellular Vesicles Promote Recovery Following Spinal Cord Injury via Improvement of the Integrity of the Blood-Spinal Cord Barrier - Lu, Yanhui; Zhou, Yan; Zhang, Ruiyi; Wen, Lulu; Wu, Kaimin; Li, Yanfei; Yao, Yaobing; Duan, Ranran; Jia, Yanjie (Frontiers in Neuroscience, 2019)
Mesenchymal stem cell (MSC) transplantation has been shown to be a potential treatment for traumatic spinal cord injury (SCI). However, there are several obstacles that need to be overcome before MSCs can be considered for clinical application, such as failure of MSCs to reach the spinal cord lesion core and possible tumor formation. Recent studies have suggested that MSC treatment was beneficial due to paracrine-secreted factors. Of these, exosomes are considered to be one of the most valuable paracrine molecules. However, the effect of exosome administration on recovery from SCI is still unclear. Therefore, our study was designed to investigate the effect of systemic administration of exosomes on the loss of motor function after SCI and examine a potential mechanism of effect. Disruption of the blood spinal cord barrier (BSCB) is a crucial factor which is detrimental to motor function recovery. Pericytes are an important component of the neurovascular unit, which play a pivotal role in maintaining structural integrity of the BSCB. Our study demonstrated that through bone mesenchymal stem cell-derived exosomes (BMSCs-exos) administration, the neuronal apoptosis was reduced, the neuronal survival and regeneration was enhanced, motor function improved compared with sham group and BMSCs-exos-free conditioned media(exos-free CM).Besides, BSCB was attenuated and pericyte coverage was significantly decreased in vivo.Furthermore, we found that exosome treatment reduced pericytes migration via down-regulation of NF-kB p65 signal, with a consequent decrease in permeability of the BSCB.In summary, we identified that exosome treatment promoted migration of pericytes and further improved integrity of BSCB via targeting the NF-kB p65 signal in pericytes. Therefore, our data suggests that exosomes may serve as a promising treatment strategy for SCI.